2021
DOI: 10.3389/fimmu.2021.670561
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal Broadly Neutralizing Antibody Activity Characterized by CD4 Binding Site and V3-Glycan Antibodies in a Subset of HIV-1 Virus Controllers

Abstract: Broadly neutralizing antibodies (bNAbs), known to mediate immune control of HIV-1 infection, only develop in a small subset of HIV-1 infected individuals. Despite being traditionally associated with patients with high viral loads, bNAbs have also been observed in therapy naïve HIV-1+ patients naturally controlling virus replication [Virus Controllers (VCs)]. Thus, dissecting the bNAb response in VCs will provide key information about what constitutes an effective humoral response to natural HIV-1 infection. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The kinetics of the biomolecular interactions were examined by immobilizing the ligand on an appropriate sensor surface and keeping the analyte in solution ( Figure 1A ). Antigens were loaded onto Streptavidin (SA) or Aminopropylsilane (APS) or Amine reactive (AR2G) biosensors as detailed previously for testing the binding antibodies ( 8 , 11 13 , 22 ). For this method, the form of the antibody will influence the kinetics of binding to the immobilized antigen as demonstrated by differences in the kinetics of epitope-matched Fab and IgG1 (Fab form, Figure 1B ; IgG1 form, Figure 1C ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The kinetics of the biomolecular interactions were examined by immobilizing the ligand on an appropriate sensor surface and keeping the analyte in solution ( Figure 1A ). Antigens were loaded onto Streptavidin (SA) or Aminopropylsilane (APS) or Amine reactive (AR2G) biosensors as detailed previously for testing the binding antibodies ( 8 , 11 13 , 22 ). For this method, the form of the antibody will influence the kinetics of binding to the immobilized antigen as demonstrated by differences in the kinetics of epitope-matched Fab and IgG1 (Fab form, Figure 1B ; IgG1 form, Figure 1C ).…”
Section: Methodsmentioning
confidence: 99%
“…Sample analyses were performed with approval from the Duke Medicine Institutional Review Board for Clinical Investigations (Protocol Pro00074497, Pro00104803 and Pro00009701). The efficacy and/or immunological evaluations for these studies were reported earlier ( 8 , 11 , 13 , 22 , 29 31 ). All study participants had previously provided consent for future use of samples for research, and all samples were de-identified.…”
Section: Materials and Equipmentmentioning
confidence: 99%
See 3 more Smart Citations